The definition of vitality—the perspectives of Dutch older persons - M. E. Jongeneelen; C. H. L. A. Wieringa; W. P. J. den Elzen; K. Langeveld; J. Gussekloo; Y. M. Drewes (BMC Public Health)
Abstract Background Vitality is often mentioned in the context of successful ageing, however, there is still no consensus on the definition of vitality. Moreover, older persons themselves have yet to be involved in establishing a definition of vitality. Aim To explore and describe how older persons define vitality, how they experience vitality, and what influences their vitality. Method A qualitative study consisting of 33 semi-structured interviews with community-dwelling older persons (60 +) in the Netherlands. The interviews were analysed using the thematic content analysis. Results The definition of vitality that emerged from the interviews was “vitality is having the physical, cognitive, and social capacities to do what you want to do”. The important dimensions of vitality can be divided into their capacities and their drivers in life. The capacities consisted of physical, cognitive, and social capacities. Sustaining these three capacities was important for the preservation of vitality. Main drivers in life were autonomy, independence, and meaning in life. Their experience of vitality was mostly determined by the balance between their capacities on one side and their drivers in life on the other side. Furthermore, this balance, and therefore their vitality, could be impacted by their lifestyle, loss of social network, coping, and role models. Conclusion According to older persons, vitality is determined by the balance between their capacities to do what they want to do on one side, and their drivers in life on the other side.